Resource-Based Thinking as a Means of Implementation of Personality’s Creative Potential - Mergalyas M. Kashapov (National Research Mordova State University, 2017)
Introduction: the authors consider the resource-based thinking as a means of implementing the creative potential of personality. The relevance of the study is caused by the absence of theoretical and empirical research works about the resource-based thinking as a cognitive process of revealing the best ways to solve problems in a variety of areas of activities. The purpose of article is to conduct the empirical research and theoretical substantiation of a subject’s resource-based thinking capable to show initiative in search for the new and to be able to take the responsibility for process and result of cogni tive-transformative activity. Materials and Methods: the Life Line technique by A. A. Kronik and E. I. Golovakha was used in the research; a qualitative analysis of the empirical data was carried out; a synthesis of previously obtained results of the resource-based thinking study was achieved. Results: the resource-based thinking has a variable effect on the implementation of the personal creativity. The subsequent development of a person depends on the level of maturity of resource-based thinking in different stages of his/her life. The resource-based thinking can be a means of realising the personality’s creative potential or a means of their extinction depending on the congruence of potentials with the most important life events. Discussion and Conclusions: the resource-based thinking of a professional is associated with cognitive selfsupport and promotes a positive interpretation of the situation and a constructive change in self-perception. An analysis of certain life events influenced the future of a man, his personal development and formation in society is made. The conceptual basis of resource-based thinking with a description of functions, structural components, resource conditions, as well as the specifics of their formation and stages of implementation is presented. Understanding the resource-based essence of a man as a fundamental characteristic of his/ her being is developed. The practical significance lies in finding reference points in formation of personal structures by means of social identification that make possible creation of resources for oneself and for the others. Resource-based thinking as key competence of a subject allows to provide possibilities of participation in the socially useful cognitive-transformative activity and to critically assess it. Optimum distribution of resources promotes effective use of resources for activity and life-creation, including scheduling of events and their managing for achievement of definite purposes.